Getting Ready for Work: KarierKu Application for Students of Public High School 1 Ungaran - Anggraini, Weni; Suwidagdho, Dhanang; Wicaksono, Damar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
SMA N 1 Ungaran faces several priority issues related to students’ career maturity, including a low understanding of student’s interests and personality types, as well as a lack of information about further study options and types of work. Students have difficulty in determining a suitable career, coupled with a lack of effective communication between students and parents. The proposed solutions include training on improving career maturity and effective communication with parents, as well as the development of a website-based application called KarierKu. The implementation of the activity began with socialization activities for students and teachers regarding the activity plan and the development of the KarierKu application. The KarierKu is mobile-friendly and provides six main menus: Consultation, My Plan, RIASEC Test, List of Universities, List of Professions, and SNBP Mapping. These menus support students in choosing career and education paths, as well as facilitating consultations with guidance and counseling teachers. The next activity is the use of the KarierKu carried out to parents and students which is also related to improving communication between parents, students, and guidance and counseling teachers. The next activity is assistance in using the KarierKu. This service activity produces a KarierKu that can be used by counseling teachers, students, and parents to increase career maturity. Furthermore, there is an increase in student career maturity before and after the activity. It can be concluded that the use of the KarierKu in training activities can improve the career maturity of SMA N 1 Ungaran students.